2007
DOI: 10.1111/j.1742-1241.2007.01544.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient-controlled sedation vs. anaesthetic nurse-controlled sedation for cataract surgery in elderly patients

Abstract: Both ACS and PCS using propofol provided reduced anxiety compared with control, but patient's satisfaction was higher in the PCS group compared with ACS group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
0
8
2
Order By: Relevance
“…They found this ratio to be closer to one in the PCS/fuzzy-control group compared with the physician administered analgesia group. This is in contrast to Yun who found a higher demand/delivery ratio (more demands/fewer deliveries) in a highly satisfied cataract PCS group compared with the nurse-sedated group [34]. This suggests that this metric may not be a useful measure of sedation adequacy; the mere act of pressing the button may be clinically significant.…”
Section: Clinical Experiencecontrasting
confidence: 64%
See 2 more Smart Citations
“…They found this ratio to be closer to one in the PCS/fuzzy-control group compared with the physician administered analgesia group. This is in contrast to Yun who found a higher demand/delivery ratio (more demands/fewer deliveries) in a highly satisfied cataract PCS group compared with the nurse-sedated group [34]. This suggests that this metric may not be a useful measure of sedation adequacy; the mere act of pressing the button may be clinically significant.…”
Section: Clinical Experiencecontrasting
confidence: 64%
“…Ganapathy et al [31], in a study of elderly patients undergoing joint arthroplasty with regional AE propofol PCS, noted a tendency toward oversedation with PCS in older patients. In contrast, Yun et al [34] found enhanced patient satisfaction and no significant complication difference in the use of propofol PCS for cataract sedation in the elderly. This difference may be partly explained by the short duration and low dose regimen required for cataract surgery.…”
Section: Clinical Experiencementioning
confidence: 91%
See 1 more Smart Citation
“…But there are also a need for randomized studies of the optimal dose of propofol and its effect on safety and the need for interventions. With no lockout period, propofol doses of 3.33 mg, 21 and 4 mg, 22 has been used, and with a lock-out period of one minute doses of 10 mg, 23 17 mg 24 , and 20 mg 20 . Both strategies reported episodes of hypoxemia and required manipulation of the patients' airway to avoid serious events.…”
Section: Discussionmentioning
confidence: 99%
“…In one trial, patient-controlled sedation was administered in elective ophthalmologic day-surgery with a high level of patient satisfaction and no adverse effects on cognitive function [56], but the technique has not yet been validated in other studies. Perioperative sedation by dexmedetomidine infusion may be superior to other sedatives in reducing the incidence of POD [57,58], the effect on POCD is yet not elucidated.…”
Section: Anaesthetic Managementmentioning
confidence: 99%